Global Uncertainty: The Influence of Monetary Policies Order and Inflation Volatility on Bank Profitability African Bank and Middle East Bank - Firmansyah, Bayu; Fajar Fardiansyah, Aldi; Dhevyanto , Benny (Journal Research of Social Science, Economics, and Management, 2024)
The objective of this paper is to examine the factors that influence the resilience and adaptability of banks to economic disruption. The aim is to encourage a collaborative and cooperative approach to these challenges. This study analyses the impact of monetary policies, inflation trends, and bank-specific determinants on bank profitability in the African and Middle Eastern regions. A quantitative research approach was used to assess macro and micro factors affecting bank profitability, using secondary data. The macro variables were obtained from the International Monetary Fund (IMF), and the micro variables were extracted from the banks' annual accounts. The research findings indicate that monetary policy and inflation have significant impacts on banks' profitability. Additionally, the System Generalized Method of Moments (GMM) model revealed that the annual interest rate (IR), inflation (INF), capital adequacy ratio (CAR), and previous financial performance (Lagged ROA/ROE) have positive and significant effects on both ROA and ROE. In addition, the loan-to-deposit ratio (LDR) had a significant positive effect on ROE, while the non-performing loan ratio (NPLr) had a significant negative effect. The validity and suitability of the GMM regression model used in this study were confirmed by the AR(2) and Sargan Test results. These findings provide valuable insights for decision-makers in the banking sector to respond to changes in monetary policy and manage risks associated with inflation fluctuations. The study emphasizes the importance of capital management and credit risk management in sustaining bank profitability amidst economic uncertainty.